Serbest Ticaret Anlaşmalarının Türkiye’nin Dış Ticaretine Etkileri - Adem Doğan; Ahmet Uzun (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Turkey signs free trade agreements in order to accomodate to the EU common trade policy. Turkey has so far signed 29 free trade agreements. The seventeen agrements is in force at the moment. Turkey’s main expactation of these free trade agreements is to increase the volume of trade with the countries in question, that is the countries with which an agreement was made. Between 2000-2012, the rate of increase of Turkey's export to the countries with which a free trade agreement are made, exceeded the overall rate of increase in exports of Turkey. The same is valid for import. Consequently, it seems that Turkey’s main expectation has realized. On the other hand, it is worthy of note that the rates of increase in exports to these countries, and in imports from these countries don't show large deviations from the rates of increase in Turkey's overall exports and imports.